Preparation of a PVDF/PVDF-g-(PSSS-co-PAA) graft copolymerization-blending cation exchange material and effects of the synthesis method on the material structures and properties - S. W. Sun; X. L. Gao (eXPRESS Polymer Letters)
In this study, a PVDF/PVDF-g-(PSSS-co-PAA) graft copolymerization-blending cation exchange material was synthesized with polyvinylidene fluoride (PVDF), sodium p-styrene sulfonate (SSS) and acrylic acid (AA) by the methods of solution polymerization and suspension polymerization, based on the preparation of cation exchange materials. Experimental results indicated that the exchange capacity was well designed, and that water absorption and water swelling could be effectively controlled. The morphology of the modified material was analyzed by SEM, which showed that the material had a uniform particle size. Thermal analysis of the material demonstrated that the material synthesized in N,N-dimethylformamide (DMF) had excellent thermostability and good compatibility with PVDF.